Optimization of recycled polypropylene concrete aggregates processing using water-assisted melt compounding via response surface methodology - Mohamad, Noraiham; Abd Ghani, Anis Aqilah; Anen, Marvrick Anak; Abd Razak, Jeefferie; Raja Abdullah, Raja Izamshah; Mohd Ali, Mohd Amran; Ab Maulod, Hairul Effendy; Se, Sian Meng (2023)
Plastic waste aggregate for concrete is a vast communicating topic nowadays due to overusing and depletion of natural sands and gravels. Despite efforts, plastic waste aggregates (PWA) still weaken concrete due to inadequate particle interaction. Incorporating clay particles into plastic particles is a wise step to mitigate this issue. Water-assisted melt compounding is a